Durability studies of Spent Mushroom Compost Ash (SMCA) as partial cement replacement in concrete - Loh, Huang Ming (2017)
Concrete had become competitive building material due to its huge versatility and comparative economy in meeting wide range of demands. Added to this is the need to withstand the escalating cost and scarcity of cement. Meanwhile, mushrooms have been regarded as one of the high-value commodities under Malaysia's National Agro-Food Policy (2011-2020). With the growth of mushroom industry, mushroom industry waste are expected to increase. From the entire spent mushroom compost generated in Malaysia, 69 % is thrown in landfill sites. In addition, Malaysia largely depends on open dumping and landfills, where most of these sites have exceeded its operating capacity, leading to serious environmental and social threats. It is therefore vital for the industry to discover alternative waste management of the spent mushroom compost. The aim of this work is to study the durability performance concrete on the application of spent mushroom compost ash (SMCA) as partial cement replacement. Replacement level of 10 % Ordinary Portland Cement (OPC) by SMCA was chosen for the concrete mixes. Design strength of 30 MPa with water-cement ratio of 0.45 was used. The specimens are cast and cured for 28 days before being tested for water absorption, sorptivity, acid resistance, sulphate resistance and chloride resistance. All results are compared with normal concrete. It is demonstrated that SMCA concrete performed better than normal concrete in water absorption with 0.003 % vs. 0.012 % and 0.005 mm/√min vs. 0.138 mm/√min in sorptivity. The percentage weight changes of SMCA concrete are also lower than normal concrete in acid resistance and sulphate resistance with 0.06 % vs. 0.13 % and 0.04 % vs. 0.19 % respectively. However, normal concrete is more resistant than SMCA concrete in chloride exposure for 28 days with percentage weight gain of 0.067 % vs. 0.072 %. The results indicate pozzolanic reaction in the SMCA concrete.